Comparative Study of Information Security Awareness and Practice Within Home and Work Environments: Case Study in Libya - Tamtam, Abdalmonem; Asker, Hamida (European Scientific Journal, ESJ, 2024)
The abundance of information available through the internet, mobile applications, and cloud computing has made it convenient for users to access a wide range of data. However, this convenience comes at a cost, as this information is constantly at risk of being compromised by cybercriminals and hackers. While the recognition of potential information security dangers is increasing in developed countries, regions like Libya in North Africa still exhibit insufficient protection levels. The purpose of this study is to compare various factors that may influence or affect users' practices and awareness in home and work environments. Specifically, the factors investigated are policy, behavior, IT knowledge, and education. To achieve the study's goals, a quantitative methodology was employed, and a survey was created to assess the correlation between these key factors and security awareness and practices in home and workplace settings. The survey attracted 220 respondents and was analyzed using statistical methods to determine the relationship between the independent variables and the dependent variables. The results of this study indicate a moderate positive correlation between policy, IT knowledge, and education with security awareness and practice in both home and workplace environments. Only the behavior factor had a low correlation for home users. These findings indicate that the level of security awareness and practices at home and in the workplace is generally moderate. This study aims to serve as an initial step in emphasizing the importance of security training sessions for employees and highlighting the need to increase knowledge of information security. The findings are intended to inspire further research and focus on providing security information to the public, thereby disseminating new knowledge on the importance of security training and enhancing awareness of information security.